Anaerobic degradation of catechol by Desulfobacterium sp. strain Cat2 proceeds via carboxylation to protocatechuate. - Gorny, N (1994)
Under anoxic conditions, most methoxylated mononuclear aromatic compounds are degraded by bacteria, with catechol being formed as an important intermediate. On the basis of our experiments with the sulfate-reducing bacterium Desulfobacterium sp. strain Cat2, we describe for the first time the enzymatic activities involved in the complete anaerobic oxidation of catechol and protocatechuate. Results obtained from experiments with dense cell suspensions of strain Cat2 demonstrated that all enzymes necessary for protocatechuate and benzoate degradation were induced during growth with catechol. In addition, anaerobic oxidation of catechol was found to be a CO2-dependent process. Phenol was not degraded in suspensions of cells grown with catechol. In cell extracts of Desulfobacterium sp. strain Cat2, protocatechuyl-coenzyme A (CoA) was formed from catechol, bicarbonate, and uncombined CoA. This oxygen-sensitive reaction requires high concentrations of both bicarbonate and protein, and only very low levels of enzyme were detected. In a second oxygen-sensitive step, protocatechuyl-CoA was reduced to 3-hydroxybenzoyl-CoA by reductive elimination of the p-hydroxyl group. Further dehydroxylation to benzoyl-CoA was not detectable. Key reactions described for anaerobic degradation of benzoate were catalyzed by cell extracts of strain Cat2, too.